Hydrodynamic Lift in the sculling [rowing] stroke - Young, K. (1997)
It's been long controversial in the rowing community if and how much lift occurs in the sculling stroke. The data has been sparse. We can consider several factors: a) consistency of force production with lift versus drag force In the drag force case, the blade must be moving backwards [relative to still water] in order to generate the thrust. F = A*Cd*1/2 *density*v^2. b) production of an isolated single major vortex during the beginning of the stroke. Aerodynamic [hydrodynamic] theory requires that a single vortex be produced upon the acceleration of an air foil. The paired vortex remains circulating on the foil until the foil is stopped. You may investigate this further in the lift.html web page.